Further constituents of Vernonia cineria leaves - Augustine A. Ahmadu, Adebola Onanuga (Journal of Applied Pharmaceutical Science, 2015)
The genus Vernonia consists of over 1000 species and members of the genus are widely used as food and medicine. As part of our continuing research into ethnomedicinal plant of Nigeria for bioactive plant metabolites, the leaves of Vernonia cineria was investigated for phytochemical constituents. The pulverized leaves of Vernonia cineria were extracted with 70% ethanol and the crude ethanolic extract was suspended in water and partitioned with n-hexane, ethyl acetate and n-butanol. The n-hexane and ethyl acetate soluble parts which showed similar spots on thin layer chromatography were pooled together and coded V1. Extensive column chromatography of V1 afforded the triterpenoids: Lupenol and Oleanan-12.15 dein-28-oic acid. The structures were elucidated using NMR an MS and compared with literature. The oily fraction was subjected to GC-MS equipped with library data to give fatty acids and long chain hydrocarbons. Antibacterial investigation of the ethanol extract at concentration in the range 5-50 mg/ml against the clinical isolates of S. aureus, B. subtilis, E. coli and P. aeruginosa did not show any activity.
Keywords: Vernonia cineria, triterpenoids, fatty acids.